The single-cell atlas of short-chain fatty acid receptors in human and mice hearts - He, Xiaojun; Wang, Qiang; Long, Qiang; Zhong, Yiming; Qi, Zhaoxi; Zhang, Yecen; Chang, Lan; Qian, Bei; Huang, Shixing; Wang, Xinming; Chen, Xuemei; Li, Feifei; et al. (Frontiers in Immunology, 2025)
IntroductionThe gut microbiota metabolite, short-chain fatty acids (SCFAs), can protect against multiple cardiovascular diseases, while the molecular targets and underlying mechanisms need to be elucidated. One of the primary mechanisms of SCFA benefits was the direct activation of a group of G-protein-coupled receptors (GPCRs), termed free fatty acid receptors (FFARs), the FFAR2 (GPR43), and FFAR3 (GPR41). At present, the distribution of FFAR2/3 in cardiac cells has not been entirely clarified.MethodsUsing 18 public single-cell RNA-seq and single-nuclear RNA-seq data of human and mouse hearts, we illustrate the entire atlas of FFAR2/3 distribution in different regions and cell types in normal and infarcted hearts.Results and discussionWe present the atlas of FFAR2/3 in the whole human body, normal and infarcted hearts at single-cell resolution. We also illustrated the entire atlas of FFAR2/3 in normal/ischemic hearts of newborn and adult mice by combining public and newly built sc/snRNA-seq datasets. These findings provide valuable information on the possible effect of SCFAs via FFAR2/3 in the heart and valuable references for future studies.